Znaczenie ruchu rodziców w procesie emancypacji osób niepełnosprawnych intelektualnie - Koperski, Łukasz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
This article consists of three parts. The first made the characteristics of paradigm shifts in the perception of intellectual disability – from the medical model to the social and political and disability in terms of emancipation. The second part is dedicated to the rear movement of parents of persons with disabilities in a sociological theory of social movements and contemporary understanding of new forms of community. The third section presents the most important stages of development of the movement of parents of persons with disabilities in Poland since the 60s to today, indicating the author's classification functions that they perform in the context of emancipation. The author at the beginning of the article poses the question of the role of parents in motion the creation of conditions for the emancipation of people with intellectual disabilities.At the same time it indicates that the movement of the parents may contribute to the emancipation of people with disabilities, by presenting them as autonomous individuals who deserve equal treatment, to support their autonomy and strengthening the sense of agency. Initiatives taken by the parents, or established with their participation entities, they tend to emphasize the role of socio professional people with intellectual disabilities. The change at the same time is the media image of the same disabilities as people with talents, skills, resources or social skills at a high level. On the other hand, the movement of the parents may also contribute to the limitations of the emancipation of people with intellectual disabilities. The emphasis on the social question could result in the presentation and reception with disabilities as dependent, in need of constant care – a consequence as a category helpless in life and socially. Indication of the emancipation of people with disabilities through active participation of parents in the public discourse enables better draw public attention to disability, which may contribute to the better understanding.